(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article analyzes the research of scientists who studied the work of retaining walls under different soil conditions, and their contact interaction with the base. Examples of recent designs of retaining walls and their use are given. It is stated that the goal is to study the stress-strain state of a retaining wall with a structural surface, considering its contact interaction with the ground mass. The main stages and features of mathematical modeling of the retaining walls and soil foundation interaction in the conditions of a flat problem with the help of LIRA 9.6 software have been described. As a result, the nature of the retaining wall work has been analyzed under various conditions of interaction with the base and with different parameters of the retaining wall rigidity. The relationship between the retaining wall rigidity and the resulting equivalent stresses in the soil foundation under various conditions of interaction has been established. It has been concluded that on the contact surface of the retaining wall with a structural surface, the effect of stresses redistribution is achieved and the carrying capacity of the foundation soil is increased due to the formation of elastic cores and unloading arches.